Synthesis and Biological Properties of Zinc(II)Complexes of some 2-hydroxyacetophenone-benzoylhydrazones - M. Ali, Hapipah; Abdul Halim, Siti Nadiah; P, Subramaniam; S.M, Zain; W, Jefri Basirun; Ismail, Endom; Abdullah, Noorlidah; H.L, Teoh (Malaysian Journal of Science, 2006)
The new zinc(II) complexes have been prepared in ethanol by condensation of 2-hydroxyacetophenone with either benzhydrazide or 3-methoxybenzhydrazide and zinc acetate in the presence of triethylamine. The IR, Â¹H, Â¹Â³C NMR and UV-visible data show coordination of hydrazone ligands to the metal centers and the spectroscopic data augur well with the x-ray structures which had been published earlier. The Schiff bases and their complexes were screened for antimicrobial, cytotoxic and antioxidant activities. The anti-microbial activities of the ligands and complexes were evaluated by using plate diffusion method against some gram-positive bacteria, gram-negative bacteria and two fungi. There was growth inhibition exhibited by ligands and zinc(II) complexes against tested bacteria and fungi. The Schiff base, Hâ‚‚hapbh was cytotoxic with ICâ‚…â‚€ 10.0 Âµgmlâ»Â¹ against the MCF-7 (human breast cancer cells) while both zinc(II) dimer complexes were strongly cytotoxic with ICâ‚…â‚€ values of 4.5 Âµgmlâ»Â¹. The Schiff bases and zinc(II) complexes showed higher antioxidant activity than quercetin or vitamin E and is comparable with butylated hydroxy toluene (BHT), a commercially used synthetic antioxidant.